Influence of FYM and inorganic fertilizers on growth and yield of isabgol (Plantago ovata Forsk) - B K Yadav, T Choudhary, S K Sharma, (Journal of Spices and Aromatic Crops, 2014)
A field experiment was conducted to assess the effect of inorganic fertilizers and organic manure on plant growth and seed quality of isabgol in a hot arid region. Plant growth parameters viz., plant height, number of tillers plant-1 and dry matter accumulation was significantly higher with NPK + FYM as compared to other treatments. Yield attributes such as spike length, number of spikes plant-1 and number of grains spike-1 were also significantly higher with NPK + FYM. Highest grain (13.40 q ha-1) and straw (30.21 q ha-1) yield was obtained with the application of NPK + FYM, which was at par with NPK + Zn. Application of NPK + FYM recorded the highest N, P and K contents. However, highest Zn content was observed with NPK + Zn. The highest protein content in grain (12.43%) and straw (5.13%) was found with the treatment NPK + FYM, which was at par with NPK + Zn. The results clearly showed that the application of inorganic fertilizers significantly increase isabgol yield, nutrient content and grain quality when applied with organic manure as compared to sole application of inorganic fertilizers.